THU0157 Comparison of Clinical Outcomes between Rheumatoid Arthritis Patients under TNF Inhibitors Using A Tapering Strategy or Standard Therapy Regimen in Daily Clinical Practice. (10th June 2014) - Plasencia, C.; Wolbink, G.; Krieckaert, C.; Kneepkens, E.; Turk, S.; Bonilla, M.; Villalba, A.; Nurmohamed, M.; Diego, C.; Martín-Mola, E.; Pascual-Salcedo, D.; Balsa, A.
Abstract : Background: There is sparse evidence about the disease control after longterm tapering of TNF inhibitors (TNFi)in rheumatoid arthritis (RA)patients (pts) Objectives: To compare the clinical outcomes in RA pts on tapering strategy with RA patients on standard regimen of TNFi with a longterm followup Methods: In this observational study 144 RA pts under TNFi therapy [infliximab (Ifx), adalimumab (Ada) or etanercept (Etn)] were included. Two groups were compared: Group1 (67 pts from Spain) on tapering strategy and Group2 (77 pts from Netherlands) on standard therapy. Pts were matched on duration of inactive disease before inclusion and duration of the follow-up. Disease activity had to be low (DAS28<3.2) for at least 6 months before inclusion. The tapering strategy included dose reduction and/or interval elongation, however if a flare occurred treatment could be intensified. The clinical activity was measured by DAS28 at different time points: visit-0 (at baseline, just before starting the biological), visit-1 (Group1: just before starting tapering; Group2: after at least 6 months in low disease activity) and visit-2 (the last visit available after visit-1) Results: Sixty seven RA pts were in tapering group (Group 1: 23 with Ifx, 23 with Ada and 21 with Etn) and 77pts in control group (Group 2: 22 with Ifx, 27 with Ada and 28 with Etn). Most pts were rheumatoid factor positive [52/67 (77.6%) in Group 1 vs 58/75 (77.3%) in Group 2, p=0.968]. No significant differences were seen in disease duration (years) (16.49±7.17 in Group1 vs 17.49±7.79 in Group 2, p=0.489), time (years) in inactive disease before visit-1 (1.14±0.95 in Group 1 vs 0.92±0.54 in Group 2, p=0.421) and following (years) between visit-1and visit-2. (2.38±1.17in Group 1 vs 2.41±0.86 in Group 2, p=0.327). No statistical differences were found in clinical activity (DAS28) and percentage of patients with flares (see Table). Although the dropout was similar in both groups, the secondary inefficacy was more frequent in the tapering group (see Table).The overall drug administered was reduced in tapering group at visit-2 in comparison with the group on standard therapy regimen (an elongation in administration interval of 32.8% in Ifx, 52.9% in Ada and 52.6% in Etn) Conclusions: The tapering strategy in a cohort of RA patients with inactive disease results in an important reduction in the drug administered while the clinical course is similar to a RA cohort without tapering. However, a small percentage of RA patients on tapering seems to be more prone to dropout due to secondary inefficacy Disclosure of Interest: : C. Plasencia Grant/research support: Pfizer, G. Wolbink Grant/research support: Pfizer, Speakers bureau: Pfizer, Amgen, C. Krieckaert Speakers bureau: Abbvie, Pfizer, E. Kneepkens: None declared, S. Turk: None declared, M. Bonilla: None declared, A. Villalba: None declared, M. Nurmohamed Grant/research support: Abbvie, BMS, MSD, Pfizer, UCB, Roche, Consultant for: BMS, Pfizer, Roche, Speakers bureau: Abbvie, Pfizer, Roche, C. Diego: None declared, E. Martín-Mola Speakers bureau: Abbvie, UCB, Pfizer, Roche, D. Pascual-Salcedo Grant/research support: Pfizer, Speakers bureau: Pfizer, A. Balsa Grant/research support: Pfizer, Speakers bureau: Pfizer, Abbvie, Roche DOI: 10.1136/annrheumdis-2014-eular.2133